Fatty Acids in Natural Ecosystems and Human Nutrition - Gladyshev, Michail I. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Long-chain polyunsaturated fatty acids (PUFAs) of the omega-3 family, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are physiologically important for many animals and humans. Moreover, fatty acids play an important roles in numerous contexts reflecting various levels: from their producers in natural ecosystems, microalgae, through to invertebrates and fish, and to culinary treatments of fish products for human consumption. Environmental threats such as anthropogenic pollution and its effects on PUFA yield in aquatic ecosystems as well as their transfer to terrestrial ecosystems are highlighted. Assumptions and challenges that are important for the study of PUFA in trophic webs of aquatic ecosystems as well as in human nutrition are discussed.